Forms and Consequences of the Cyber Threats and Extortion Phenomenon - Vasiu, Ioana; Vasiu, Lucian (European Journal of Sustainable Development, 2020)
Cyber threats and extortionate communications usually aim to influence the behavior or obtain compliance from victims. The phenomenon includes a wide range of forms, such as intimate partner violence; violence against women; dating abuse; sexual harassment; sexual coercion and extortion; etc. The victimization is linked to personal insecurity or disruption, mental and physical health, work or school performance, may represent a high financial burden, affecting negatively the sustainable development in a number of ways. The scale, scope, and challenges posed by this criminal phenomenon cannot be overstated. A deep analysis of the nature and extent of cyber extortion and threat is an essential component in the design of control strategies and programs. This research aims to provide an in-depth examination of the cyber threats and extortion phenomenon. The approach is interdisciplinary and empirically-informed. The analysis was done on a large number of cases and provides a comprehensive description of the essential characteristics of the phenomenon, including forms, communication vectors, and consequences for victims. The article concludes with recommendations for effectively addressing the phenomenon. Keywords: Cybercrime, Extortion, Speech, Threats, Violence, Discrimination, Ransomware